(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
The purpose of this essay is to elaborate a definition of behavior in Radical Behaviorism. It is argued that a definition of behavior would take into account (1) the philosophical grounding of Radical Behaviorism, (2) the behavior’s dynamic, and (3) the relation among events, states, and process. Starting from the relational interpretation, this essay defends that behavior can be concept as a relation organism-environment, whose dynamic is a sensory-motor co-ordination. As this dynamic result, we have a behavioral stream, which can be analyzed in terms of an interdependence relation among environmental events, behavioral events, behavioral states, and behavioral process.